Endoscopic Removal of Inflated Transected Sengstaken-Blakemore Tube Using Endoscopic Scissors - Jun Ho Lee; Eu-Kwon Hwang; Chanmesa Doeun; Jeong-Ju Yoo; Sang Gyune Kim; Young Seok Kim (Korean Society of Gastrointestinal Endoscopy, 2019)
Balloon tamponade using Sengstaken-Blakemore (SB) tube is employed as a bridging therapy in cases in which endoscopic therapy fails to control esophageal variceal bleeding. Although SB tube insertion can lead to successful hemostasis, it is accompanied by numerous complications, with SB tube transection being one of the rarest complications. A 53-year-old man with liver cirrhosis and hepatocellular carcinoma presented with massive esophageal variceal bleeding. Therapeutic endoscopic variceal ligation failed, and SB tube was inserted. The SB tube was unexpectedly disconnected because of the patient's irritability due to hepatic encephalopathy. The esophageal and gastric balloon of the SB tube remained inflated in the stomach. Whereas the use of other endoscopic instruments was ineffective, endoscopic removal was successfully accomplished using endoscopic scissors. In conclusion, we detected SB tube transection in a patient with hepatic encephalopathy and removed remnants of the inflated tube using endoscopic scissors.